Trends in rotator cuff repair rates and comorbidity burden among commercially insured patients younger than the age of 65 years, United States 2007-2016 - Elizabeth L. Yanik, PhD, ScM (Elsevier, 2021)
Background: Prior US studies have shown increasing rotator cuff repair rates through 2009. We hypothesize that rotator cuff repair rates are continuing to increase and the comorbidity profiles of patients are becoming more complex over time. Methods: We identified rotator cuff repairs in a large US cohort of people 18-64 years of age with ≥1 year of commercial insurance coverage. Repair rate trends across time were standardized by age, sex, and geographic region. Procedures were categorized as inpatient vs. outpatient and as arthroscopic vs. open. Prevalent comorbidities were defined as 1 inpatient diagnosis claim or 2 outpatient diagnosis claims during the year before rotator cuff repair. General population comorbidity prevalence was determined based on a random 5% sample of the commercially insured population and compared with patients with rotator cuff repair using standardized morbidity ratios. Results: From 2007 to 2016, 314,239 rotator cuff repairs were identified (165 repairs per 100,000 person-years). Rotator cuff repairs were performed more frequently in men, older people, and in the Midwest. Across time, cuff repair rates increased by 1.6% per year (95% confidence interval [CI] = +1.4%-1.7%) adjusting for demographics. The highest increases in repair rates were observed among patients aged 50-64 years (+2.0%, 95% CI = +1.8%-2.2%). Rotator cuff repairs were more frequently performed using an arthroscopic approach and in an outpatient setting in later calendar years. In 2016, 83% of rotator cuff repairs were arthroscopic procedures and 99% were performed as outpatient procedures. Comorbidity prevalence in rotator cuff repair patients increased across calendar time by 4.5% per year for hypertension (95% CI = +4.2%-4.7%), 2.3% per year for diabetes (+1.9%-2.7%), 0.9% per year for hypercholesterolemia (+0.3%-1.5%), 2.9% for congestive heart failure (+0.8%-4.9%), 4.2% for peripheral vascular disease (+2.4%-6.0%), and 4.2% for chronic pulmonary disease (+3.6%-4.8%). Comorbidity prevalence in repair patients was higher than prevalence in the general population, and prevalence relative to the general population was most heightened during later calendar years. For example, hypertension prevalence was 1.58 times higher in repair patients than the general population in 2007 (95% CI = 1.53-1.62), and 2.06 times higher in 2016 (95% CI = 2.02-2.11). Conclusion: Rotator cuff repair is becoming more frequent in the US commercially insured population, particularly in those 50-64 years of age. More rotator cuff repairs are being performed using an arthroscopic approach and in an outpatient setting. Over time, the comorbidity profile of patients undergoing rotator cuff repair is becoming more complex with greater prevalence of numerous conditions, including hypertension, peripheral vascular disease, and chronic pulmonary disease.